Study of A Spiritual Pedagogic Concept Based on A Western Perspective and The Hadith of The Qur'an and Its Implications - Nurrena Ulayyah; Aam Abdussalam (Nazhruna: Jurnal Pendidikan Islam, 2022)
The rise of crime cases that occur among students shows that current educational progress does not go hand in hand with the morals of students. This is because the learning activities carried out only focus on the cognitive and psychomotor aspects of students and tend to ignore the affective side of students. Therefore, a study of spiritual pedagogy as a way to develop students' effectiveness needs to be done. This study aims to examine the concept of spiritual pedagogy based on the Western perspective and the Qur'an and hadith and its implications for IRE learning. This research was conducted using a qualitative approach with a literature study method, namely through books, journals, and sources related to spiritual pedagogy. From this study, it was found that spiritual pedagogy, both according to the western perspective and the Qur'an and hadith both involves values ​​in its implementation. The difference is that values ​​in a western perspective can come from culture, religion, or knowledge. Meanwhile, based on the Qur'an and hadith, the value in question is the values ​​that already exist in humans, not external values ​​which are then crammed into them.